2020
DOI: 10.1021/acs.jafc.0c04620
|View full text |Cite
|
Sign up to set email alerts
|

HLB-MCX-Based Solid-Phase Extraction Combined with Liquid Chromatography–Tandem Mass Spectrometry for the Simultaneous Determination of Four Agricultural Antibiotics (Kasugamycin, Validamycin A, Ningnanmycin, and Polyoxin B) Residues in Plant-Origin Foods

Abstract: An ultrahigh-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) method was established for the determination of four highly polar agricultural antibiotics kasugamycin, validamycin A, ningnanmycin, and polyoxin B in plant-derived foods. The samples were extracted with a 0.2% formic acid solution, purified by hydrophilic–lipophilic balance and mixed-mode cation-exchange solid-phase extraction, and then reconstituted for UPLC–MS/MS detection. The chromatographic analysis was performed on a BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…Nevertheless, it was reported that the retention time and sensitivity were excellent, and because of confirming this, sufficient retention time and sensitivity were secured, as shown in Fig. 1(c) [7,10,19]. Therefore, in this study, an amide column highly effective for kasugamycin was selected and analyzed.…”
Section: Establishment Of Lc/ms/ms Analysis Conditionssupporting
confidence: 52%
See 4 more Smart Citations
“…Nevertheless, it was reported that the retention time and sensitivity were excellent, and because of confirming this, sufficient retention time and sensitivity were secured, as shown in Fig. 1(c) [7,10,19]. Therefore, in this study, an amide column highly effective for kasugamycin was selected and analyzed.…”
Section: Establishment Of Lc/ms/ms Analysis Conditionssupporting
confidence: 52%
“…Water was selected as the final extraction solvent in% with the highest recovery rate (Table S1). The extraction of kasugamycin from dried samples using methanol and water was previously reported, and the recovery rate found increased as the water content increased [7]. Therefore, in this study, 10 mL of distilled water was added to the sample (5 g), followed by a wetting process for 1 h, and then extracted with 40 mL of water adjusted to pH 4.5-5 by adding 0.1% formic acid solution.…”
Section: Establishment Of Extraction and Distribution Processmentioning
confidence: 87%
See 3 more Smart Citations